PENGARUH KEBIJAKAN PERKEBUNAN TERHADAP PENANAMAN MODAL ( PMDN DAN PMA ) (studi kasus perkebunan kelapa sawit di Provinsi Riau) - Masheri "; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the effect of farm policy towards domestic investment and foreign investment in the province of Riau. Investment in the plantation sector in Riau province is part of the purpose of the investor as well as the geographic and regulatory support, global history of the emergence of the first foreign investment in Europe in 1760. The role of investment is helping the movement of the economy, then the researchers wanted to see Indonesia managing investments in domestic investment and foreign investment in the oil palm sector in the province of Riau.This research used a descriptive analytical method, in this study the data were compiled using data integration techniques Primary and secondary data. secondary data in the form of journals, mass media, books, research, Internet, and electronic media, the primary data used in this study in the form of data from agencies and legislation.Plantation policy and investment policy is a policy alignment reality in favor of investors. The lack of regulation in favor of the ruling capitalist society makes the system in the management of existing plantations in Indonesia, especially in the province of Riau.Keywords: plantation policy, domestic investment, foreign investment